2016
DOI: 10.1136/acupmed-2015-010947
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Controlled Trial of Contralateral Manual Acupuncture for the Relief of Chronic Shoulder Pain

Abstract: Objective To explore the effects of contralateral manual acupuncture (MA) on patients with chronic shoulder pain. Methods Eighty patients with chronic shoulder pain were randomly allocated to receive contralateral MA (n=38) for 4 weeks or to remain on a waiting list while receiving conventional orthopaedic therapy (n=42). Visual analogue scale (VAS) scores were taken as the primary outcome measure and used for a priori power calculation. Secondary outcome measures for the assessment of shoulder mobility and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Thus, it is unclear how long the brain changes related to acupuncture treatment at the contralateral or ipsilateral acupoint persist in chronic shoulder pain. However, our findings are consistent with a randomized controlled trial of subjects receiving contralateral acupuncture for 4 weeks, which demonstrated beneficial effects of contralateral acupuncture in the treatment of chronic shoulder pain, both in terms of pain and function [9]. Finally, although the purpose of this study is to uncover the different neural mechanisms of contralateral and ipsilateral acupuncture at ST 38, evaluating the mechanisms of bilateral acupuncture will help to understand the neural plasticity central function.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Thus, it is unclear how long the brain changes related to acupuncture treatment at the contralateral or ipsilateral acupoint persist in chronic shoulder pain. However, our findings are consistent with a randomized controlled trial of subjects receiving contralateral acupuncture for 4 weeks, which demonstrated beneficial effects of contralateral acupuncture in the treatment of chronic shoulder pain, both in terms of pain and function [9]. Finally, although the purpose of this study is to uncover the different neural mechanisms of contralateral and ipsilateral acupuncture at ST 38, evaluating the mechanisms of bilateral acupuncture will help to understand the neural plasticity central function.…”
supporting
confidence: 88%
“…Due to poor agreement on diagnostic criteria and the lack of specificity of clinical assessment that is considered a "gold standard", no uniform, specific treatment protocol exists [7,8]. Acupuncture, as a complementary alternative treatment, has been used in the treatment for CSP in China and has been also accepted for pain management in Western medicine [9]. The advantage of acupuncture for CSP is the lower incidence of adverse effects compared to pharmacy treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effectiveness of taping therapy was evaluated by the following measures: termination of taking needed medications, normalization of pulse, alleviation of impairing symptoms (eg, anger, aggressiveness, sedation, suicidality, and homicidality), and improvement in the patients’ ratings on the visual analog scale (from 10 [worst] to 1 or 0 [perfect satisfaction] in all cases) used widely in clinical studies. 14 16 …”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of this taping therapy was evaluated using the following measures: change in radial pulse and symptoms, termination of taking medications, and the patients’ ratings on the visual analog scale (10: worst and 0: perfect satisfaction). 14 16 …”
Section: Case Presentationmentioning
confidence: 99%
“…Improvement of symptoms was evaluated by the patient, using a visual analog scale (VAS) ranging from 0 (perfect satisfaction) to 10 (most severe or discomfort) [10][11][12]. Termination of medications, maintenance of a down-regulated, resting radial pulse, alleviation or disappearance of symptoms and, a decrease in the area or intensity of painful responses were all considered as evidence of progressive improvement.…”
Section: Evaluation Of Improvementmentioning
confidence: 99%